A STUDY OF ACEH LOCAL WISDOM COMMUNICATION IN THE ART OF MEURUKON COLLABORATION BETWEEN ART AND DA'WAH - Ismail, Muchlis; Hasan, Kamaruddin; Jamiati; Akmal, Fitria; Isma, Yuli Santri (FISIP Universitas Malikussaleh, 2025)
Communication is an important process of conveying messages. Because communication is integrated with various things related to human interaction in everyday life. The sajrone interaction process develops understanding through the way the message is delivered, including the aesthetic aspect to the impression of the sajrone communication process, namely dhewe. the art of Meurukon mujudake salah sawijine tradhisi Acehnese ing art sing nggabungake art of poetry because of the content of the value of the religious message which is combined with various meanings and semiotics through the media which are used with various kinds of poetic expressions which are considered to fulfill the principles of the saka tradition of speaking. Meurukon arts serve as an educational means for the people of Aceh to learn the elements of Minangka art and preaching the complete unity of the norms, customs and values of community unity.